AN INCREASING INCIDENCE OF INJURIES DURING THE SUPER RUGBY TOURNAMENT: A PROSPECTIVE STUDY OVER 4 YEARS INVOLVING 69 194 PLAYER-HOURS. Issue 4 (1st February 2017) - Schwellnus, Martin; van Rensburg, Dina Christina Janse; van Rensburg, Charl Janse; Jordaan, Esme; van Rensburg, Audrey Jansen; Derman, Wayne; Readhead, Clint
Abstract : Background: Rugby Union has one of the highest reported incidences of match injuries among all professional sports. The Super Rugby tournament is played annually between professional rugby union teams from three rugby-playing nations in the Southern hemisphere. Objective: To determine if the incidence of injuries in the Super Rugby tournament decreased over a 4-year period. Design: Prospective cohort study. Setting: Super Rugby tournament. Patients (or Participants): 774 male players from 5 South African teams. Assessment of Risk Factors): Medical staff of South African teams participating in the 2012, 2013, 2014 and 2015 tournaments recorded all time loss injuries (all injuries and match injuries) and exposure hours (69 194 total playing hours; 6 132 match hours). Main Outcome Measurements: Incidence of all injuries and match injuries (per 1000 hours play). Results: The incidence of all injuries (per 1000 player hours; 95% CI) for each year was as follows: 2012 (9.2; 7.9–10.8); 2013 (11.6; 10.1–13.3); 2014 (11.4; 9.8–13.2), and 2015 (12.4; 10.9–14.1). The incidence of all injuries in 2015 was significantly higher compared to 2012. The overall incidence of match injuries (per 1000 player hours; 95% CI) for each year was as follows: 2012 (83.3; 69.4–99.2); 2013 (120.4; 103.6–139.2); 2014 (98.6; 83.3–116.0), and 2015(119.1; 102.9–137.2). The incidence of match injuries in 2013 and 2015 was significantly higher compared to 2012 and 2014. Conclusions: There is an increased incidence of all injuries and match injuries in the Super Rugby tournaments between 2012–2015. After 2012, the incidence of match injuries is consistently higher than previously reported for senior male rugby players at elite/professional level (89–96 per 1000 hrs). There is an urgent need to introduce targeted injury prevention strategies in the Super Rugby tournament to reduce the risk of injuries.